Pemanfaatan DAS Brantas dalam Konteks Pelaksanaan Program Revolusi Hijau di Jawa Timur Masa Orde Baru - Endrayani, Eko Crys; Krisnadi, Ignatius; Nawiyanto; Suharto; Handayani, Sri Ana; Salindri, Dewi (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2023)
This article discusses the utilization of the Brantas River Basin in the context of implementing the Green Revolution program in East Java during the New Order era which made an important contribution to the success of the New Order government in getting out of the food crisis and becoming self-sufficient in rice. Wlingi Dam (Blitar Regency) and Widas Dam (Nganjuk Regency) were successfully built thanks to the collaboration between the Indonesian government and the Japanese government as funders and as consultants for the development of modern agriculture in Indonesia. The two dams are useful in irrigation systems, flood control, converting dry land to paddy fields, conserving and breeding fish and becoming tourist destinations for the Brantas watershed in East Java.